2015
DOI: 10.1039/c4cc08436e
|View full text |Cite
|
Sign up to set email alerts
|

A thermostable transketolase evolved for aliphatic aldehyde acceptors

Abstract: Directed evolution of the thermostable transketolase from Geobacillus stearothermophilus based on a pH-based colorimetric screening of smart libraries yielded several mutants with up to 16-fold higher activity for aliphatic aldehydes and high enantioselectivity (>95% ee) in the asymmetric carboligation step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 32 publications
5
63
0
Order By: Relevance
“…Among further residues, which were identified to influence stereoselectivity, is phenylalanine in standard position 434 found in Ec TK, Gst TK and Sc TK and conserved with 62 % in the whole TK superfamily . Also leucine in standard position 382 is conserved among these TKs and found in 61 % of all sequences of the TK superfamily. Besides, an isoleucine found in Ec TK and Sc TK in standard position 189 is replaced by L191 in Gst TK .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among further residues, which were identified to influence stereoselectivity, is phenylalanine in standard position 434 found in Ec TK, Gst TK and Sc TK and conserved with 62 % in the whole TK superfamily . Also leucine in standard position 382 is conserved among these TKs and found in 61 % of all sequences of the TK superfamily. Besides, an isoleucine found in Ec TK and Sc TK in standard position 189 is replaced by L191 in Gst TK .…”
Section: Resultsmentioning
confidence: 99%
“…Also leucine in standard position 382 is conserved among these TKs and found in 61 % of all sequences of the TK superfamily. Besides, an isoleucine found in Ec TK and Sc TK in standard position 189 is replaced by L191 in Gst TK . Aspartate in standard position 469 plays a role in substrate binding, activity enhancement and stereoselectivity, is conserved among the three TKs mentioned above and found in 59 % of TK sequences.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive comparative analysis of the substrate tolerance of TK Gst showed that non‐α‐hydroxylated aldehydes are accepted by wild‐type TK Gst with activity 40 times lower than that towards the corresponding α‐hydroxylated derivatives (Scheme ) . The removal of the α‐hydroxy group reduces the number of possible hydrogen‐bonding contacts between TK and acceptor substrate and might also affect the catalytic efficiency and the stereoselectivity of TK Gst . Thus, a structural adjustment based on mutagenesis of the residues in the active site that make contact with the substrate might help to improve the binding and activation of non‐α‐hydroxylated substrates.…”
Section: Methodsmentioning
confidence: 99%
“…At the position opposite Asp470, Leu382 provides a hydrophobic contribution to substrate binding. Therefore, in our previous study, these two key residues were chosen as the preferred mutagenesis positions for the creation of a double‐site saturation mutagenesis library, out of which the top variant—L382F/D470—has specific activity towards propanal 11 times higher than that of the wild type, yielding the 3 S product with high ee (>95 %) . However, all of the positive variants from this library were found to maintain the stereopreference for the 3 S configuration, except for the variant L382I/D470L, which showed inversed stereoselectivity but only with a very low ee (9.4 %) .…”
Section: Methodsmentioning
confidence: 99%
“…For applications in biocatalysis, lithium hydroxypyruvate (HPA) is used as the donor substrate because the reaction becomes irreversible by the decarboxylation of HPA and the release of bicarbonate ions. Since TKs from different microbial sources can accept a wide range of hydroxylated and non-hydroxylated aliphatic, [4][5][6][7] and cyclic and aromatic aldehydes, 4,8 they represent a highly attractive biocatalytic platform technology for the synthesis of chiral polyols, (3S)-ketoses, with an ever-increasing range of applications [8][9][10][11][12] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%